Information processing and its relationship to the performance of offensive skills in basketball for students of the Department of Physical Education at the University of Zakho - Ahmed, Ali (Humanities Journal of University of Zakho, 2021)
The importance of the current study In students’ ability to process information and also the learner’s ability to work with the information he receives from theoretical lessons in understanding, concentration, remembering and perception, and his reliance on different patterns in order to classify this information as well as analyze it and then store it in order to be retrieved meaning it is practically applied when needed.And then learn the role of information processing in the performance of offensive skills with basketball. The aim of the study is to identify the relationship (Information processing and its correlation with the performance of offensive basketball skills among students of the Physical Education Department at the University of Zakho). The researcher used the Descriptive Method in a correlational method to suit it with the objectives and the problem of the study, and the study population consisted of (109 students) at the University of Zakho/ Faculty of Education/ Department of Physical Education for the academic year 2020-2021. As for the methods of data collection for the study, it included scale (Information Processing) and offensive skills tests for basketball (Shooting, Passing, Dribbling) with Criteria finding in terms of (Validity, Reliability, Objectivity) for the scale as well as for skill tests. For the statistical treatment of data, the researcher used the SPSS V.26 statistical bag. The most important conclusions reached by the researcher are (the existence of a high correlation between information processing and the skills of Shooting Passing Dribbling for basketball, the ability of students to process information).